2016
DOI: 10.1186/s12887-016-0607-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of published trials: long-term safety of topical corticosteroids and topical calcineurin inhibitors in pediatric patients with atopic dermatitis

Abstract: BackgroundMany clinicians have concerns about the safety of atopic dermatitis (AD) treatments, particularly in children requiring long-term daily maintenance therapy. Topical corticosteroids (TCS) have been widely used for >5 decades. Long-term TCS monotherapy has been associated with adverse cutaneous effects including atrophy, rebound flares, and increased percutaneous absorption with potential for adverse systemic effects. Topical calcineurin inhibitors (TCIs), tacrolimus and pimecrolimus, available for 1–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 80 publications
3
124
0
8
Order By: Relevance
“…A recent systematic review of AD patients less than 12 years of age found that the evidence supporting long-term TCS use is limited only to low- to mid-potency agents, and there was a lack of data supporting the use of long-term monotherapy with mid- to high-potency TCS in pediatric AD [60]. In fact, continuous, long-term application of high- and very high-potency agents can lead to significant systemic absorption and increased risk of systemic adverse effects, such as hypothalamic-pituitary-axis (HPA) suppression, especially in children concurrently receiving other forms of steroids for asthma [61].…”
Section: Treatmentmentioning
confidence: 99%
“…A recent systematic review of AD patients less than 12 years of age found that the evidence supporting long-term TCS use is limited only to low- to mid-potency agents, and there was a lack of data supporting the use of long-term monotherapy with mid- to high-potency TCS in pediatric AD [60]. In fact, continuous, long-term application of high- and very high-potency agents can lead to significant systemic absorption and increased risk of systemic adverse effects, such as hypothalamic-pituitary-axis (HPA) suppression, especially in children concurrently receiving other forms of steroids for asthma [61].…”
Section: Treatmentmentioning
confidence: 99%
“…Basically, lowto-mid potency TCS should be used as first-line treatment. No TCS is indicated for > 4 consecutive weeks of use (21).…”
Section: Topical Corticosteroidsmentioning
confidence: 99%
“…Другие авторы в обзоре за последние 10 лет [40] сообщи-ли, что местное применение тГКС не приводило к разви-тию глаукомы и катаракты. Тем не менее стоит опасаться длительного нанесения тГКС на тонкую и нежную кожу лица, век, а также в крупных естественных складках [40].…”
Section: топические глюкокортикостероидыunclassified